Curie isotherm map of Indian subcontinent from satellite and aeromagnetic data - Rajaram, M.; Anand, S.P.; Hemant, K.; Purucker, M.E. (My University, 2009)
Estimating depth to the bottom of the magnetic crust (synonymously called the Curie isotherm) on a regional scale from long wavelength magnetic anomalies requires that large areas of survey data be used for the calculations. There is still no consensus on the minimum survey area required to arrive at a reliable estimate of the Curie isotherm depth. From the available aeromagnetic data over India, depth to the Curie isotherm is estimated using spectral techniques. We found that the significant spectral maxima required to calculate the depth to the Curie isotherm existed only for 4° × 4° blocks in southern peninsular India up to 18 °N latitude and for 5° × 5° blocks for the rest of the region in Central India. As aeromagnetic data coverage over India is incomplete, we also calculate the magnetic crustal thickness from the lithospheric model of the CHAMP satellite data for the whole country, using an iterative forward modeling approach. The calculated Curie isotherm is shallow in the mobile belts and deeper in the cratons in both the derivations. As the Curie isotherms calculated from the two data sets collected at very different altitudes using totally different techniques, match reasonably well, it lends credence to the methodology adopted. The derived Curie isotherm depth map is in accordance with the basic structural trend of the major tectonic units within the Indian subcontinent. A comparison is made of the calculated Curie isotherm depth with Moho depths along available DSS profiles over India and it is found that the Curie depth is generally shallower than the Moho depth implying that it possibly represents a thermal boundary rather than a compositional change. Further, we find that high magnitude earthquakes are associated with high gradients in Curie depth.
Keywords: Aeromagnetic data; Curie isotherm; Spectral methods; CHAMP